DEVELOPMENT OF THE EARLY WARNING SYSTEM MODEL ON THE PERFORMANCE OF BANK PERKREDITAN RAKYAT (BPR) - Titin Ruliana; Imam Nazarudin Latif; Meiki Permana; Jihan Irana Dewi (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study aims to analyze the role of the Early Warning System (EWS) in predicting bankruptcy at Bank Perkreditan Rakyat (BPR). The EWS is viewed as an early detection mechanism capable of identifying financial and non-financial indicators that could potentially lead to bankruptcy risk. This study uses historical BPR data to develop an EWS-based prediction model. This study uses a quantitative approach and empirical methodology. The quantitative approach was chosen because it allows for objective measurement of financial variables and testing of relationships between variables using statistical techniques in SEMPLS. The population in this study is all BPR operating in the East Kalimantan region and officially registered with the Financial Services Authority (OJK), with an observation period starting from 2019 to 2025. The implications of this research emphasize the importance of implementing an EWS as an effective risk management tool for rural banks (BPRs) and providing input to regulators in strengthening the banking supervisory system. Thus, the EWS serves not only as an early warning system but also as a strategic instrument in maintaining the stability and sustainability of BPRs amidst local and national economic dynamics.